2012
DOI: 10.20355/c5b59j
|View full text |Cite
|
Sign up to set email alerts
|

Content-Based English Education in China: Students’ Experiences and Perspectives

Abstract: This study explores undergraduate students’ experiences and perceptions of the content-based EFL instruction at a northwestern Chinese university. It is one of the first empirical studies of content-based EFL in China. Through a three-part open-ended questionnaire administered with 34 undergraduate students majoring in finance, the study reveals overwhelming support for this approach to EFL. Participants believed that learning English and content knowledge simultaneously was helpful and that the spread of Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…1 Internationalisation of higher education policies in Japan evaluations of universities as a performance indicator; those providing at least 10% of all courses in English rated as 'excellent' . The policy was revised in 2007, increasing the percentage to 10% of undergraduate credits to be delivered in English (Beckett and Li 2012;Zhang 2017). Of the 135 HEIs across mainland China, 132 had provided EMI courses/programs by 2006, averaging 44 per institution (Wu et al 2010, cited in Hu et al 2014.…”
Section: English Medium Instruction: a Growing Trendmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Internationalisation of higher education policies in Japan evaluations of universities as a performance indicator; those providing at least 10% of all courses in English rated as 'excellent' . The policy was revised in 2007, increasing the percentage to 10% of undergraduate credits to be delivered in English (Beckett and Li 2012;Zhang 2017). Of the 135 HEIs across mainland China, 132 had provided EMI courses/programs by 2006, averaging 44 per institution (Wu et al 2010, cited in Hu et al 2014.…”
Section: English Medium Instruction: a Growing Trendmentioning
confidence: 99%
“…In Japan, Aizawa and Rose (2019) also found it to be a major deterrent for students. English proficiency has been reported to be a significant factor in determining the success of an EMI programme (Ball and Lindsay 2013;Beckett and Li 2012;Doiz et al 2014;Llurda 2013;Wilkinson 2013) and students' English proficiency has been related to a number of issues in the EMI classroom (Airey 2011;Airey and Linder 2006;Beckett and Li 2012;Chapple 2015;Hellekjaer 2010;Tsuneyoshi 2005). These include problems understanding lessons and lectures, communicating disciplinary content, asking/answering fewer questions, taking longer to complete the course and an increased chance of dropping out.…”
Section: Emi Policy Implementation and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most important factors affecting the successful implementation of EMI in Japan are those of a linguistic nature, starting with the level of English language proficiency students possess. Insufficient ability has been identified as a major impediment to successful EMI courses in numerous previous studies (e.g., Beckett & Li, 2012;Doiz et al, 2012;Webb, 2002). As a consequence, research has shown that students lacking ability to keep up tend to participate less in the classroom (Webb, 2002), have considerable difficulty comprehending lessons (Tsuneyoshi, 2005;Hellekjaer & Räsänen, 2010), take longer to complete their courses (Tsuneyoshi, 2005), and are more likely to drop out (Selzer & Gibson, 2009 classes failed to complete them and either gave up or officially withdrew.…”
Section: Linguistic Issuesmentioning
confidence: 99%